ETNISITAS DAN POLITIK LOKAL PROVINSI LAMPUNG (Study Kasus Etnisitas pada Pemilukada Lampung Selatan 2010) - M, Dega Okta (Journal of Politic and Government Studies, 2014)
In the political arena in the district / city , competition between local and ethnic immigrants looks verystrong . Regional Head Election ( Election ) June 30, 2010 , held simultaneously in five districts / cities inLampung has prove it . The combination of Java and Lampung ethnic almost always arise until thegeopolitical characteristics of an area in Lampung could be represented on the winner of Regional HeadElection . In Metro Citie majority ethnic Javanese , for example , Lukman Hakim and Saleh Chandra Javabloody win the General Election . In Pesawaran district the ethnic composition was balanced betweenLampung and Java , the winner is Aries Password ( Lampung ) and Musiran ( Java ) . The same case is seenin East Lampung , although with suspect status , Satono , was dominate sound among 60 percents in themiddle of Java bloody . In South Lampung regency with dominant Lampung ethnic composition thanJavanese , so winning the Regents and Vice Regents elected, they are Waki Rycko Menoza SZP - EkiSetyanto . The purpose of this study is to determine " the role of ethnicity in the general election in SouthLampung regency at 2010â€. The research methods are qualitative - descriptive type because descriptivestudies systematically describe a situation , problem , phenomenon , service or program , the provision ofinformation about a situation , problem , social life , or describe the attitude of the people responding to aparticular issue.